Teaching philosophies in Puppet Theatre Puppeteer – actor-puppeteer - performer (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2018)
At first – terminology. The words should respond to their designates. So the puppet theatre means theatre in which puppet (as a three dimentional figure of the real or fantastic beings) dominates. All the other phenomena like shadow, hand or objects theatre should have their own names to exclude the terminological chaos. Thus the paper speaks on teaching of real puppeteer working within the real puppettheatre. There are four type of puppeteers: 1. natural one – a nugget, 2. taught within the theatre or at various courses, 3. puppeteer- actor taught in the higher academiesaccording to the drama principle, 4. a virtual puppeteer-performer, taking his impulses from the fine art and the energy of the matter. As the experiment with actor-puppeteer’s teaching failed the performer might be real puppeteer of the future.Keywords: Puppet. Puppeteer. Actor. Performer. Material puppet theatre.